Mongol, Muslim, Rajput: Mahimāsāhi in Persian Texts and the Sanskrit Hammīra-Mahākāvya - Bednar, Michael Boris (Journal of the economic and social history of the Orient, 2017)
The life of a Mongol named Mahimāsāhi underwent a series of transformations in Persian and Sanskrit texts. Mahimāsāhi was born a Mongol, became a New Muslim, and died a Kshatriya Rajput warrior in 1301. With time, he moved from history into historical memory. This historical memory was further transformed by literary conventions in Sanskrit and Persian texts. While Mahimāsāhi represents a Mongol threat in Persian texts, he embodies the warrior’s duty in the Sanskrit Hammīra-Mahākāvya and serves as an example for others on how to become Rajput.